Restoring natural killer cell activity in lung injury with 1,25-hydroxy vitamin D3: a promising therapeutic approach - Amer, Johnny; Salhab, Ahmad; Abuawad, Mohammad (Frontiers in Immunology, 2025)
Background and aimNK cells and NK-cell-derived cytokines were shown to regulate neutrophil activation in acute lung injury (ALI). However, the extent to which ALI regulates lung tissue-resident NK (trNK) activity and their molecular phenotypic alterations are not well defined. We aimed to assess the impact of 1,25-hydroxy-vitamin-D3 [1,125(OH)2D] on ALI clinical outcome in a mouse model and effects on lung trNK cell activations.MethodsOleic acid (OA)-induced ALI in C57BL/6J mice and 1,25(OH)2D treatment 2×/2 weeks were performed. Lung tissue was harvested to assess alveolar I/II cell apoptosis and lung injury marker of Surfactant-Protein-D (SP-D). Pulmonary edema markers of epithelial sodium channel, cystic fibrosis transmembrane conductance regulator, and aquaporin 5 were assessed by RT-PCR. Lung trNK cells were assessed for activation markers of CD107a and NKp46, vitamin D receptor (VDR), and programmed cell death protein-1 (PD-1) via flow cytometry. The bronchoalveolar lavage fluid (BALF) obtained was investigated for soluble receptor for advanced glycation end products (sRAGE), inflammatory cytokines, soluble 1,25(OH)2D, and PDL-1. Naïve mice treated with DMSO (vehicle) were used as a control.ResultsFlow cytometry analysis displayed a high apoptotic rate in alveolar I/II cells of threefold in ALI mice as compared to naïve mice. These findings were accompanied by elevated markers of pulmonary edema as well as lung injury markers of SP-D. Isolated lung trNK cells of the ALI mice exhibited reduced CD107a and NKp46 markers and cytotoxicity potentials and were correlated through significantly 2.1-fold higher levels of PD-1 and diminished VDR expressions as compared to naïve mice. BALF samples of ALI mice displayed high soluble PDL-1 and reduced soluble 1,25(OH)2D levels compared to naïve mice. 1,25(OH)2D treatment alongside OA led to a significant fourfold increase in the CD107a and NKp46 expressions to levels higher than the mice treated with the vehicle. Furthermore, 1,25(OH)2D ameliorates free radical scavengers of GSH, GPX, CAT, and GPx-1; decreased pro-inflammatory cytokines and soluble PDL-1; and increased soluble 1,25(OH)2D with amelioration in pulmonary edema markers and alveolar I/II apoptosis.ConclusionOur results indicate 1,25(OH)2D’s potential therapeutic effect in preventing clinical outcomes associated with ALI via regulating NK cells through inhibiting inflammatory cytokines and alleviating levels of PDL-1 and 1,25(OH)2D released by lung tissue.